Emotional Intelligence Through Mathematical Resilience on Secondary Students Based on Gender - Ayu Faradillah; Silvi Wulandari (Jurnal Pendidikan dan Pengajaran, 2021)
The low mathematical resilience of students, one of the factors is the fear of being wrong so that it shows things related to students' emotions. Mathematical resilience and emotional intelligence are interrelated, therefore students need to develop mathematical resilience and emotional intelligence to be ready to face challenges and be able to learn optimally. The purpose of this study is to analyze mathematical resilience on students' emotional intelligence based on gender in twelve different schools. The method used is descriptive qualitative. The population of this study was 814 students consisting of 301 male students and 513 female students. The selection of subjects in this study by looking at the category of Mathematical Resilience, namely high, medium and low. Subjects were selected using the Winsteps application by looking at the wright map table. From the total population, the researcher chose three subjects to be studied in depth. Furthermore, the selected subjects were asked to fill out an Emotional Intelligence questionnaire and interviewed by the researcher. The results of the analysis of ST who have high Mathematical Resilience have high Emotional Intelligence, ST are able to control themselves and have high interest in learning mathematics, SS who have moderate Mathematics Resilience have moderate Emotional Intelligence. In the learning process, SS does not focus on learning and is less able to explore its potential in depth. SR who have low Mathematical Resilience have low Emotional Intelligence as well. SR tends to give up easily and has low learning motivation. However, it should be noted that there is no gender difference in Emotional Intelligence, because this is based on the instrument or measuring instrument used in the study.